Integration of P, S, Fe, and Zn nutrition signals in Arabidopsis thaliana: potential involvement of PHOSPHATE STARVATION RESPONSE 1 (PHR1) - Briat, Jean-François; Rouached, Hatem; Tissot, Nicolas; Gaymard, Frédéric; Dubos, Christian (Frontiers in Plant Science, 2015)
Phosphate and sulfate are essential macro-elements for plant growth and development, and deficiencies in these mineral elements alter many metabolic functions. Nutritional constraints are not restricted to macro-elements. Essential metals such as zinc and iron have their homeostasis strictly genetically controlled, and deficiency or excess of these micro-elements can generate major physiological disorders, also impacting plant growth and development. Phosphate and sulfate on one hand, and zinc and iron on the other hand, are known to interact. These interactions have been partly described at the molecular and physiological levels, and are reviewed here. Furthermore the two macro-elements phosphate and sulfate not only interact between themselves but also influence zinc and iron nutrition. These intricated nutritional cross-talks are presented. The responses of plants to phosphorus, sulfur, zinc or iron deficiencies have been widely studied considering each element separately, and some molecular actors of these regulations have been characterized in detail. Although some scarce reports have started to examine the interaction of these mineral elements two by two, a more complex analysis of the interactions and cross-talks between the signaling pathways integrating the homeostasis of these various elements is still lacking. However, a MYB-like transcription factor, PHOSPHATE STARVATION RESPONSE 1 (PHR1), emerges as a common regulator of phosphate, sulfate, zinc and iron homeostasis, and its role as a potential general integrator for the control of mineral nutrition is discussed.